Teknik Prompting untuk Meningkatkan Keterampilan Konsep Uang dan Aktivitas Ekonomi pada Anak dengan Disabilitas Intelektual Sedang - Anita Carolina Hendarko; Ike Anggraika (Universitas Kristen Maranatha, 2019)
The purpose of this research is to assess effectiveness of prompting technique to improve money and economic activity skill in children with moderate intellectual disability. This research use single-case experimental A-B design. Subject of this research is a 12 years old girl with moderate intellectual disability. Data collection technique trough observation about money and economic activity skill. Data analysis trough comparition of money and enocomic activity skill before and after training. The result of this study shows a significant improvement in money and economic activity skill, from skor 3 (from 50 of task analysis/ 6%) before training become 50 (from 50 task analysis/ 100%) after training. In future research, it is necessary to consider several things: selection of prompting and caregiver involvement is important factors to supporting the training program for children. Keywords: intellectual disability, behavioral modification, prompting, money concept, economic activity